The Constitutive Science of Benedictine Literacy: The Archive of Þingeyrar Abbey in Iceland - Gottskálk Jensson (Religions, 2023)
The monastic archives of Iceland have rarely been made the subject of specific studies. This article is intended to survey the history of one such archive, belonging to the Benedictine Abbey of Þingeyrar in Northern Iceland, which was founded 1133 and dissolved 1551. Through its extraordinarily rich literary production this monastery left an indelible mark on the Northern-European cultural heritage. After the Reformation Þingeyrar Cloister remained a state-owned and ecclesiastical institution until modern times. Its archive, which is partly preserved to this day, is both the most extensive of its kind to survive in Iceland and uniquely remained in place for almost eight centuries, making it possibly the longest operated archive in the Nordic countries. The Icelanders may be better known for their sagas and mythological poetry, but their industrious literacy certainly extended to creating bureaucratic documents in accordance with the Roman tradition. French Benedictines were among the first in the world to turn the art of archival management into an academic discipline, and the Icelandic Professor Árni Magnússon (d. 1730), who is best known for his great collection of Old Icelandic manuscripts, was the first Nordic scholar to employ their methods effectively, which he used to investigate the Archive of Þingeyrar. Surveying the history of this Icelandic archive gives us insight into a constitutive science fundamental for our access to the past.